Quality of Work Life of Provincial Administration Organization Officers in Nonthaburi Provincial Administration Organization - จักรทอง, เกรียงศักดิ์; กลิ่นเกษร, สมาน (Thai Interdisciplinary and Sustainability Review, 2019)
The objectives of this research were to study the level of quality of work life of Provincial Administration Organization Officers in Nonthaburi Provincial Administration Organization and to determine factor affected their the quality of work life of Provincial Administration Organization Officers in Nonthaburi Provincial Administration Organization. The samples composed of 252 Provincial Administration Organization Officers in Nonthaburi Provincial Administration Organization from database at 1 October 2013. Data were collected by using questionnaires and statistics data were analysed by percentage, mean, one-way ANOVA for the sample group of 3 or more at the statistical significance of .05. The results indicated that Provincial Administration Organization Officers Nonthaburi Provincial Administration Organization had Quality of work life at medium level. in aspects of adequate and fair pay, a safe and healthy environment, development of human capacities, growth and security, Democracy at work, and the total life space, but social integration and social relevance at high level. According to the hypothesis is testing, it was found that different monthly incomes and division caused difference in the level of quality of work life. However, level of education, rank and working experience did not caused any difference in the level of quality of work life.